The Ethics of Criticism - Siebers, Tobin (Cornell University Press, 1990)
Tobin Siebers asserts that literary criticism is essentially a form of ethics. The Ethics of Criticism investigates the moral character of contemporary literary theory, assessing a wide range of theoretical approaches in terms of both the ethical presuppositions underlying the critical claims and the attitudes fostered by the approaches. Building on analyses of the moral legacies of Plato, Kant, Nietzsche, and Freud, Siebers identifies the various fronts on which the concerns of critical theory impinge on those of ethics.